Elastic moduli of potassium sodium niobate ceramics: Impact of spark plasma texturing. (September 2022) - Pinho, Rui; Tkach, Alexander; Carpenter, Michael A.; Noudem, Jacques; Costa, M. Elisabete; Vilarinho, Paula M.
Abstract: An alternative sintering methodology, Spark Plasma Texturing (SPT), allowed us to prepare 98.0% dense lead-free piezoelectric (K1-x Nax )NbO3 (KNN) ceramics with a homogenous microstructure of small grains. In this work, Resonant Ultrasound Spectroscopy (RUS) was used to measure bulk, K, and shear, G, moduli of SPT KNN for comparison with conventionally sintered (CS) KNN. SPT fabrication resulted in the highest elastic moduli K = 120.3 GPa (127.7 GPa for 100% density) and G = 45.47 GPa (47.2 GPa for 100% density) ever reported for KNN ceramics. Moreover, by collecting RUS data in situ as a function of temperature, phase transitions at temperatures of 464 and 688 K for CS KNN, and 443 and 643 K for SPT KNN ceramics were determined. Low acoustic loss in the stability field of the cubic phase indicated that the ceramics were mechanically robust, while high loss in the stability fields of the tetragonal and orthorhombic structures demonstrated high mobility of ferroelastic domain walls. Graphical abstract: Image, graphical abstract .